The legal and beneficial ownership conundrum in sovereign sukuk structuring - Oseni, Umar Aimhanosi (IIUM, 2015)
The past decade has witnessed the dynamics of ṣukūk structuring amidst legal complexities in cases involving enforcement of the rights of investors or ṣukūk holders in the event of default. This paper examines the legal and beneficial ownership in a typical sovereign ṣukūk structure and the specific rights of the parties under the existing practice and the classical Islamic legal framework. Specifically, the issue of public property often used in sovereign ṣukūk as the underlying asset of the transaction leaves much to be desired. Through a systematic content analysis, this study uses the qualitative legal research method to analyse a number of sovereign ṣukūk structures gathered from available ṣukūk prospectuses. The study finds that the nature of legal and beneficial ownership in ṣukūk transplanted from the conventional bonds structuring is different from the type of ownership envisaged in Islamic commercial law. It is found that the modern structure of ṣukūk products only allows for beneficial ownership to be conferred on the ṣukūk holders, and this does not contradict any principle of Islamic law when one considers the true nature of beneficial ownership under the common law. Though it literally falls short of a true sale in Islamic law in the event of default, a closer look of the legal structure reveals the true nature of beneficial ownership. The mere fact that the ṣukūk holders can have recourse against the underlying asset justifies the conferment of true ownership. Nevertheless, the stakeholders may still need to consider the use of a public property as the underlying asset of a sovereign ṣukūk. With the increasing interest of emerging economies in ṣukūk to meet their long-term financing needs, this study is expected to guide the global Islamic finance industry on Sharī‘ah and legal issues relating to sovereign ṣukūk.